New taxa and new records for Argentina of fungi from Iguazú National Park, Misiones - Lechner, Bernardo Ernesto (2006)
Galerina mycenaeformis, Lulesia lignicola and Laccaria cyanolamellata are proposed as new species, whereas Gymnopilus lepidotus, Leucopaxillus gracillimus, Marasmius viegasii, Mycena euspeirea, Mycena niveipes, Pleurocollybia praemultifolia, Agaricus endoxanthus, Pluteus subcervinus, Hypholoma aff. trinitensis, Leucoagaricus rubrosquamosus and Macrolepiota gracilenta constitute new records for Argentina.